DEVELOPMENT AND IMPLEMENTATION OF IT-RELATED MICRO-CREDENTIALS FOR STUDENTS OF PEDAGOGICAL UNIVERSITIES - Oshanova, Н.Т.; Kamalova, Г.Б.; Khamrayev, Ш.И.; Tenizbayev, Е.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
In the modern education system, micro-credentials are considered an effective tool for developing students’ flexible skills and adapting them to the requirements of the labor market. However, in pedagogical universities, the experience of developing and implementing IT-oriented micro-credentials remains insufficiently systematized. Most existing studies focus primarily on technical specializations, which leaves the specifics of developing digital competences among students in teacher education largely unexplored. Moreover, based on the Atlas of New Professions, there is a lack of practical recommendations for revising educational programs and adapting international practices. In this regard, the introduction of IT micro-credentials for students of pedagogical universities is a relevant step towards improving the quality of education, expanding access to digital resources, and preparing specialists who are in demand in the modern labor market. Research aim: to identify the scientific and methodological foundations for the development and implementation of IT micro-credentials for students of pedagogical universities, to assess their alignment with labor market requirements, and to determine pathways for integration into the educational process. Methodology: the study conducted an expert analysis of IT-related areas outlined in the Atlas of New Professions. In addition, pilot modules incorporated into curricula were examined, and a survey was carried out among students and faculty members. Based on the collected data, a structural model of micro-credentials was developed and implementation mechanisms aligned with labor market needs were proposed. Results: the study proposed a modular structure of IT micro-credentials adapted for pedagogical universities. This structure fosters the development of students’ digital competences, the formation of labor market-oriented learning experiences, and the integration of international best practices. The suggested solutions contribute to the modernization of educational programs, acceleration of digital transformation, and enhancement of the competitiveness of future educators.